OP0074 Clinical study: Frequency and manifestations of joint disease in HIV-infected patients. (23rd January 2014) - Baerlecken, N.T.; Stoll, M.; Witte, T.; Schmidt, R.E.; Meyer-Olson, D.
Abstract : Background: The frequency of joint manifestation in HIV-infected patients is unknown. Some reports suggest that musculoskeletal pain in HIV-infected patients is substantially increased with a prevalence of up to 50% of HIV-infected patients (1). Objectives: We investigated the frequency of joint diseases in HIV-infected patients in a single university-based out-patient clinic in Germany. Methods: 1098 files of HIV-infected patients who attended our out-patient clinic between 1/2004 and 12/2010 for at least for one visit were screened for the presence of a diagnosis of inflammatory or non-inflammatory joint disease. We also correlated disease duration, CD4 cell count, viral load with frequency of joint manifestations. Results: In 62 patients (5.9%) a diagnosis of a joint disease has been made. These included HIV-associated arthritis, osteoarthritis (OA), rheumatoid arthritis, ankylosing spondylitis, non-radiographic axial spondyloarthritis, reactive spondyloarthritis, psoriatic arthritis, gout arthropathy, sarcoidosis, hemophilic arthropathia, undifferentiated arthritis and septic arthritis. The most frequent joint disease in our cohort was osteoarthritis 21/1098 (1.9%) followed by spondyloarthopathies (SpA) 18/1098 (1.6%) including psoriatic arthritis and reactive arthritis. The frequency of HIV-associated arthritis was 5/1098 (0.5%), rheumatoid arthritis 2/1098 (0.2%), gout arthropathy 3/1098 (0.3%), septic arthritis 2/1098 (0.2%), hemophilic arthropathy 9/1098 (0.8%), and misc. joint diseases 2/1098 (0.2%). 13 patients with diagnosed joint disease were female and the mean age was 51±10.5 years for all patients with joint diseases. The mean age of all patients was 43 (range 19-85) yrs. At onset of disease mean ± SD age of SpA was 43±13 yrs and of OA was 47±9 yrs. The mean (SD) of CD4 count were 340/μl (±191) in SpA and 491/μl (±213) in OA at disease onset. 21/21 (100%) of OA and 14/18 (78%) of SpA had antiretroviral treatment (ART) at disease onset. Conclusions: Our data indicate that symptomatic joint disease is a frequent disease manifestation in HIV-infected patients. OA was the most common joint disease and SpA was the most common inflammatory joint disease and seems to be more frequent as compared to HIV-seronegative populations (2). In contrast, symptomatic OA was not substantially increased in our cohort as compared with historic controls (3). Our data support previous reports of an increased risk of inflammatory arthritis, especially SpA, in HIV-infection, but no increased risk for osteoarthritis. References: [1] Walker-Bone K, Lawson E, Churchill D, Gilleece Y, Fisher M, Sabin C. Prevalence, Impact and Risk Factors for Musculoskeletal Pain among HIV Infected Adults: An Epidemiologic Study. [abstract]. Arthritis Rheum 2010;62 Suppl 10:1645 DOI: 10.1002/art.29410 [2] Braun J, Bollow M, Remlinger G. Prevalence of Spondylarthropathies in HLA-B27 positive and negative blood donors. Arthritis Rheum 1998;41:58–67. [3] Lawrence RC, Felson DT, Helmick CG, et al. Estimates of the prevalence of arthritis and other rheumatic conditions in the United States. Part II. Arthritis Rheum 2008;58(1):26–35. Disclosure of Interest: None Declared